Does it matter how we measure the health of older people in places for associations with labour market outcomes? A cross-sectional study - Emily T. Murray; Jenny Head; Nicola Shelton; Brian Beach; Paul Norman (BMC, 2022)
Abstract Background Inequalities between different areas in the United Kingdom (UK) according to health and employment outcomes are well-documented. Yet it is unclear which health indicator is most closely linked to labour market outcomes, and whether associations are restricted to the older population. Methods We used the Office for National Statistics (ONS) Longitudinal Study (LS) to analyse which measures of health-in-a-place were cross-sectionally associated with three employment outcomes in 2011: not being in paid work, working hours (part-time, full-time), and economic inactivity (unemployed, retired, sick/disabled, other). Seven health indicators from local-authority census and vital records data were chosen to represent the older working age population (self-rated health 50-74y, long-term illness 50-74y, Age-specific mortality rate 50-74y, avoidable mortality, life expectancy at birth and 65 years, disability-free life expectancy at 50 years, and healthy life expectancy at 50 years). An additional two health indicators (life expectancy at birth and infant mortality rate) were included as test indicators to determine if associations were limited to the health of older people in a place. These nine health indicators were then linked with the LS sample aged 16-74y with data on employment outcomes and pertinent demographic and individual health information. Interactions by gender and age category (16-49y vs. 50-74y) were also tested. Findings For all health-in-a-place measures, LS members aged 16-74 who resided in the tertile of local authorities with the 'unhealthiest' older population, had higher odds of not being in paid work, including all four types of economic inactivity. The strongest associations were seen for the health-in-a-place measures that were self-reported, long-term illness (Odds Ratio 1.60 [95% Confidence Intervals 1.52, 1.67]) and self-rated health (1.60 [1.52, 1.68]). Within each measure, associations were slightly stronger for men than women and for the 16-49y versus 50-74y LS sample. In models adjusted for individual self-rated health and gender and age category interactions, health-in-a-place gradients were apparent across all economic inactivity's. However, these same gradients were only apparent for women in part-time work and men in full-time work. Conclusion Improving health of older populations may lead to wider economic benefits for all.